Electron drift mobility in amorphous anthrone layers - Kania, Sylwester (Wydawnictwo Politechniki Łódzkiej, 2009)
There were investigated the magnitude of the mobility and the type of the mechanism of the electron transport in the amorphous anthrone layers Enthrone (C14H10O) is the molecular crystal. The anthrone molecules due to theirs asymmetry posses permanent dipole moment, µ = 1.22 10-29 Cm. The anthrone samples were obtained by evaporation in vacuum under the pressure of the order of 10-5 Torr on glass plates with lower substrate temperatures. Structural examination of the obtained anthrone layers was made using X - ray diffraction. In order to attain that one employed an automatic diffractometer DAR. Drift electron mobility for obtained amorphous layers were determined with TOP method. Obtained results shows the almost lack of the mobility dependence due to the magnitude of the disorder, although the other results should be expected. Either obtained mobility value , less then 10-2 cm2/Vs and activation energy value on the kT level do not permit state unambiguously if we are here with hopping transport mechanism, or with the band transport with participation of the trapping states.

Badano proces transportu elektronów w warstwach. Uzyskane wyniki nie przesądzają jednoznacznie z jakim rodzajem transportu mamy do czynienia. Uzyskane wyniki mogą sugerować występowanie zarówno transportu hoppingowego, jak i transportu w paśmie z udziałem pułapek.
Ruchliwość dryftowa elektronów w amorficznych warstwach antronu